Grappling with ambiguity and contradiction: an examination of the role of reflexivity in coach education research. Issue 1 (2nd January 2018) - Crocket, Hamish
Abstract: In this article, I analyse the complex process of developing a beginner coach education programme for ultimate Frisbee (ultimate) in collaboration with New Zealand Ultimate and volunteer coaches within New Zealand's ultimate community. I construct a reflexive account of this participatory action research project, which sought to generate pedagogically informed coach education that would benefit New Zealand's ultimate community and meet Sport New Zealand's coaching policies. I focus on particular contextual challenges and opportunities, such as ultimate's lack of resourcing, and SportNZ's Coach Development Framework, and, in a reflexive manner, consider how my biography impacted this project.